The Phenomenology of the Heart in Sukhomlinsky’s Pedagogy - Andreeva, Yulia (Innovations in Pedagogy and Technology, 2025)
The article is a theoretical study based on philosophical analysis, phenomenological description, and pedagogical reconstruction: 1) the ideas of moral education related to insightful contemplation; 2) the ideas of learning related to its hidden function of cognition, which transforms into an emotional understanding and experience of the learning process as meaningful and valuable for the growing individual, as an experience of reflection, empathy, self-respect, and self-realization. An attempt was made to carry out a philosophical analysis, pedagogical interpretation, and reconstruction of V. Sukhomlinsky's pedagogical ideas, with the aim of identifying the immanent modifications of the concept of the heart, particularly the «joy of knowledge» and the «school of joy» as pedagogical ideas and methods. The study was based on the epistemology and methodology of the theory of knowledge by I. Kant, the philosophy of life and phenomenology by I. Ilyin, the axiology of education, and the pedagogy of cooperation by V. Sukhomlinsky.  Of scientific interest is the fact that V. Sukhomlinsky associates education with freedom and is convinced that education imposed from the outside, rather than coming from the heart, will not have a positive effect. V. Sukhomlinsky associates the idea of freedom and responsibility it with the rationality of choice and the ability of a person to develop themselves. A person should act according to their conscience, guided by the call of their heart, rather than by fear of punishment. The philosophy of the heart is a profound phenomenon that forms the ethical core of V. Sukhomlinsky's pedagogy. The concept of the heart is presented as a holistic, original, practice-oriented philosophy with a personal, existential, and preaching system of views on human beings and their qualities.